2020
DOI: 10.1073/pnas.1908898117
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM analysis of a feline coronavirus spike protein reveals a unique structure and camouflaging glycans

Abstract: Feline infectious peritonitis virus (FIPV) is an alphacoronavirus that causes a nearly 100% mortality rate without effective treatment. Here we report a 3.3-Å cryoelectron microscopy (cryo-EM) structure of the serotype I FIPV spike (S) protein, which is responsible for host recognition and viral entry. Mass spectrometry provided site-specific compositions of densely distributed high-mannose and complex-type N-glycans that account for 1/4 of the total molecular mass; most of the N-glycans could be visualized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
113
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(122 citation statements)
references
References 47 publications
(63 reference statements)
3
113
0
Order By: Relevance
“…proteins of viruses belonging to the Alphacoronavirus and Gammacoronavirus genera [40,44]. Considering that this region is proteolytically sensitive and has been shown to play a major role in the S protein function in other CoVs, the use of in silico modeling tools has become a useful alternative to study this region in the context of the structural organization of the protein [37,38].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…proteins of viruses belonging to the Alphacoronavirus and Gammacoronavirus genera [40,44]. Considering that this region is proteolytically sensitive and has been shown to play a major role in the S protein function in other CoVs, the use of in silico modeling tools has become a useful alternative to study this region in the context of the structural organization of the protein [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…To perform the modeling, it is first necessary to identify a suitable protein structure to be used as template, which will determine the accuracy of the predicted model. The S protein structure of several CoVs including the following have been reported previously: Alphacoronavirus: HCoV-NL63 and feline coronavirus UU4 (FCoV-UU4); Betacoronavirus: HCoV-HKU1, MHV, SARS-CoV, and MERS-CoV; Gammacoronavirus: infectious bronchitis virus (IBV); and Deltacoronavirus: porcine deltacoronavirus (PDCoV) [39][40][41][42][43][44][45]. Considering that genome and S protein alignments have showed that the SARS-CoV-2 belongs to the Betacoronavirus genus, we focused our analysis on the S structures from viruses belonging to this genus.…”
Section: Sars-cov-2 S Protein Homology Structure Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Despite the potential impact of different local protein structure on glycan processing, the overall glycosylation of SARS-CoV-2 is comparable with SARS-CoV-1 S protein and other coronavirus S proteins 4,8,9,15 . We have previously reported that a recombinant SARS-CoV-1 S mimetic also contained 32% oligomannose-type glycans showing a remarkable conservation in glycan processing across these coronaviruses.…”
Section: Fully Glycosylated Model Of the Sars-cov-2 Spikementioning
confidence: 92%
“…Antigen glycosylation greatly determines host immune responses. One of the prominent consequence of viral envelope or surface proteins is immune evasion by shield off immunogenic epitopes (Raman et al, 2016; Vigerust and Shepherd, 2007; Yang et al, 2020). The complete occupancy of glycans in most glycosite of HCoV-19 S protein suggest the virus is able to invade the host in a stealth fashion.…”
Section: Discussionmentioning
confidence: 99%